Hyperimmune egg: preparation, characterization and alternative immunotherapeutic activity - Teodora Supeanu; Madalina Tablica; Cristina Urducea; Ioana Alina Dimulescu; Lucica Sima; Viorica Chiurciu; Mariana Oporanu; Constantin Chiurciu (Medicamentul Veterinar)
The research carried out describes one preparation procedure of the monovalent and polyvalent hyperimmune eggs, obtained from hens immunized with a bacterial and fungal antigen complex, pathogenic for humans, resistant or sensitive to antibiotics. It was prepared a monovalent antigen of Staphylococcus aureus MRSA strain, isolated from a patient with urinary infection. Lots of laying hens have been formed, at the beginning of the laying period, which was immunized on days, 0, 14 and 28. From the hyperimmune eggs obtained the specific immunoglobulin Y (IgY) was extracted and purified by polyethylene glycol precipitation (PEG 6000). Purity analysis was performed by polyacrylamide gel electrophoresis in a denatured system (SDS-PAGE) obtaining a single fraction with highlighting of heavy chains (molecular weight=75KDa) and light chains (molecular weight=25KDa). By the agar gel immune-diffusion assay (IDGA), the identity between analyzed IgY and standard IgY (MyBiosurse) was highlighted. The specificity of IgY antibodies obtained from hyperimmune egg yolk was proved by the ELISA immune enzymatic assay, obtaining high titers for each antigen present in the inoculums. The hyperimmune eggs were used for the preparation of biologically active products from the range IMUNOINSTANT, recommended in the therapy of diseases caused by multi-resistant germs.